Alguém pode me ajudar resolver essa questão?
Anexos:
![](https://pt-static.z-dn.net/files/dea/c95e5d7dd3668aa91917e8af9ebb652e.jpg)
Soluções para a tarefa
Respondido por
2
Resposta:
Explicação passo-a-passo:
P(x) = x² - 4 / x - 2
P(x) = ( x + 2 ) . ( x - 2 ) / x - 2
P(x) = x + 2 ⇒ 2 + 2 = 4
Perguntas interessantes
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Sociologia,
8 meses atrás
Geografia,
10 meses atrás
História,
10 meses atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Geografia,
1 ano atrás